Biochemical profile in buffaloes with periparturient reproductive and metabolic disorders - MANDALI, G C; PATEL, P R; DHAMI, A J; RAVAL, S K; CHRISTI, K S (The Indian Journal of Animal Reproduction, 2023)
The relevant blood biochemical profile in cases ofretention offetal membranes-RFM (53), pre-partum (7) and post-partum (32) prolapse of genitalia, milk fever (25) and clinical ketosis (14) were studied and compared with those of normal (IO each) buffaloes of similar physiological status with a view to characterize the same and suggest some suitable control measures. The mean blood glucose level was significantly lower in buffaloes with RFM (53.42 ± 0.73 Vs 57.73 ± 1.42 mg%). Similarly, ketotic buffaloes also had significantly lower blood glucose (40.93 ± 0.85 Vs 58.25 ± 1.33 mg%) and higher ketone bodies (15.43 ± 0.33 Vs 3.29 ± 0.20 mg%). The serum calcium level was significantly lower in cases ofRFM (5.52 ± 0.12 mg%), pre and post-partum genital prolapse (6.27 ± 0.13 and 6.03 ± 0.13 mg%) and milk fever ( 4.30 ± 0.08 mg%,) as compared to normal ones (8.07 ± 0.2 l mg°/o). The inorganic phosphorus level was also significantly lower in pre-partum (3 .80±0.08 Vs 5.22 ± 0.15 mg°/o)and post-partum (3.29± 0.08 Vs 5.57 ± 0.12 mg%) genital prolapse and milk fever (3 .28 ± 1.0 Vs 5.57 ± 0. 12 mg%). Although magnesium levels in milk fever and total proteins and AKP levels in RFM cases did not differ from those in normal buffaloes. The serum GOT and LOH activities on the contrary were significantly higher in RFM and milk fever cases as compared to normal ones. The findings suggest that the altered metabolic profile could be the cause of most periparturient disorders in buffaloes and these could probably be prevented by proper care, balanced feeding and mineral supplements during advanced pregnancy and early post-partum period.